2016
DOI: 10.1021/jacs.6b02827
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical and Thermophoretic Analyses of the Nucleotide-Dependent Interactions between the AAA+ Subunits of Magnesium Chelatase

Abstract: In chlorophyll biosynthesis, the magnesium chelatase enzyme complex catalyzes the insertion of a Mg2+ ion into protoporphyrin IX. Prior to this event, two of the three subunits, the AAA+ proteins ChlI and ChlD, form a ChlID–MgATP complex. We used microscale thermophoresis to directly determine dissociation constants for the I-D subunits from Synechocystis, and to show that the formation of a ChlID–MgADP complex, mediated by the arginine finger and the sensor II domain on ChlD, is necessary for the assembly of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…While ATPase activity has been observed and measured for the ChlI subunit [710], no ATPase activity has been observed for ChlD. ChlI hydrolyses MgATP 2− to provide the considerable power required to drive Mg 2+ insertion [5,11]. ChlD appears to act as an allosteric regulator in response to MgATP 2− concentrations [12], and the C-terminal domain of ChlD regulates the cooperative response to Mg 2+ concentrations in the Synechocystis sp.…”
Section: Introductionmentioning
confidence: 99%
“…While ATPase activity has been observed and measured for the ChlI subunit [710], no ATPase activity has been observed for ChlD. ChlI hydrolyses MgATP 2− to provide the considerable power required to drive Mg 2+ insertion [5,11]. ChlD appears to act as an allosteric regulator in response to MgATP 2− concentrations [12], and the C-terminal domain of ChlD regulates the cooperative response to Mg 2+ concentrations in the Synechocystis sp.…”
Section: Introductionmentioning
confidence: 99%
“… 50 The interaction probability was also detected by classifying specific rupture events as possessing rupture lengths between 6 and 20 nm, whereas events with shorter or longer rupture lengths were classified as nonspecific interactions. 51 …”
Section: Methodsmentioning
confidence: 99%
“…The BchD/ChlD subunit is composed of a C-terminal integrin I domain preceded by a proline-rich region and an N-terminal domain similar to BchI/ChlI, but possesses no ATPase activity. [18][19][20][21][22][23][24][25][26][27][28] Recently, it has been demonstrated that ChlD links the ATPase activity with the ChlH active site primarily through the integrin I domain. 29 Assembly of the BchD/ ChlD hexamer is generally assumed to be mediated by the N-terminal BchI/ChlI-homologous domain, while contribution from the integrin I domain is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to limited resolution, it remains largely unknown how the hexamer is assembled. The BchD/ChlD subunit is composed of a C‐terminal integrin I domain preceded by a proline‐rich region and an N‐terminal domain similar to BchI/ChlI, but possesses no ATPase activity . Recently, it has been demonstrated that ChlD links the ATPase activity with the ChlH active site primarily through the integrin I domain .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation